Daño renal en personas con diabetes mellitus tipo II: factores de riesgo y diagnóstico precoz. Revisión sistemática - Montalvan Barreto, Jhonatan Paul (2023)
Diabetes is a chronic metabolic disease characterized by high blood sugar levels, which causes serious damage to the heart, blood vessels, eyes, kidneys, and nerves over time. The most common is type 2 diabetes, usually in adults, which occurs when the body becomes resistant to or does not produce enough insulin. The main objective of this research was to carry out a systematic review of the literature to explain the damage to kidney function, risk factors and early diagnosis in people with diabetes mellitus II. The process followed to prepare this review was: starting with the formulation of the structured question, search in databases, selection of articles, data extraction and statistical analysis, in addition, inclusion and exclusion criteria were applied. Regarding the 15 selected articles, the results obtained were the main risk factors associated with kidney disease are obesity, advanced age over 60 years, high blood pressure, hyperlipidemia, smoking, and physical inactivity also occur in the progression of diabetic nephropathy. Clinically useful tests are albuminuria and the calculation of the glomerular filtration rate, in an albumin/creatinine ratio. The equation that has the greatest prognostic value is the chronic kidney disease (CKD-EPI) equation, being the most sensitive, but the most used by clinical laboratories is the Modified Diet in Renal Disease (MDRD). Finally, as conclusions, the most important risk factors in the development and progression of diabetic nephropathy were identified, the important markers to predict the appearance and progression of early kidney disease, and the equation with the greatest prognostic value in the calculation of the glomerular filtration rate, thus resulting in the CKDEPI equation being more precise than the MDRD equation. Additional studies are needed to determine the effect of these risk factors and complications on the progression of kidney disease in T2DM and to implement programs for early detection and treatment of the disease